Comprehensive Analysis of Kaala as a Karan Dravya in Nidana Panchak: It’s Impact on Ayurvedic Diagnostic Mechanisms and Pathogenesis - Deshpande, Krishna; Gupta, Prabhanshu (Journal of Neonatal Surgery, 2025)
Nidan Panchak provides accurate information on diseases and their cures from start to finish. It aids in diagnosis, differential diagnosis, and prevention through a nutritious diet and lifestyle. Furthermore, Nidan Panchak helps with early diagnosis, understands the stages of illness, and distinguishes between diseases based on signs and symptoms. By considering medicine, diet, lifestyle, and examination methods, Upashaya is utilized to rule out diseases and ensure effective disease therapy. Protecting people from disease and death so they can live long, healthy lives is the aim of Ayurveda. It is necessary to comprehend the mechanism and the contributing elements in order to administer rational treatment or preventive treatments. Comprehensive information on the etiopathogenic factors, genesis, and etiology of diseases is provided by the Nidana Panchak. Through methodical therapy planning based on the disease's progression, pathogenesis can be eliminated. Ayurvedic teachings place a strong emphasis on understanding disease in terms of Nidana (etiology), Dosha (dysfunction), and Dushya (target tissue) stages. No matter the therapeutic approach, diagnosis is essential in every system. Ayurveda's holistic approach emphasizes considering a number of factors while reaching a diagnosis.